PENALARAN DALAM TUTURAN LISAN GURU PADA PEMBELAJARAN DI SMP KOTA MALANG - Eriyanti, Ribut Wahyu (LITERA, 2017)
Abstract This study aims to describe reasoning patterns and strategies in teachers’ language in learning at junior high schools (JHSs) in Malang City. The study used the qualitative phenomenological approach. The subjects were teachers of the Indonesian language, Science, Mathematics, and Social Studies in two public JHSs and two private JHSs in Malang City. The data were collected through observations supported by video recording devices. The results of the study are as follows. First, the reasoning patterns in teachers’ language in learning consist of: (1) Topic + Comment and Comment + Topic patterns in the sentence level; (2) (a) Main Idea (MI) + Supporting Materials (SM), (b) SM + MI, (c) SM + MI + Further Supporting Materials (FSM), and (d) SM + Implied Main Idea (IMI) in the fragment level; and (3) (a) MI + SM, (b) SM + MI + SM + MI, (c) SM + MI + SM + MI + SM, and (d) MI + SM + MI in the discourse level. Second, the reasoning strategies in teachers’ language in learninginclude: (1) deductive strategies with examples, both direct and analoguos ones; (2) inductive strategies; and (3) mixed (convergent) strategies. Keywords: reasoning, teachers’ language, learning, construction